Interaction between the forced and parametric excitations with different degrees of smallness - Dao, Nguyen Van (Vietnam Journal of Mechanics, 1998)
The nonlinear system under consideration in this paper has a specification which can be stated as an interaction between the first order of smallness no resonance parametric excitation and the second order of smallness resonance forced excitation. In the first approximation these excitations have no effect. However, they do interact one with another in the second approximation. The equations for the amplitude and phase of oscillation are found by means of the asymptotic method. The stationary oscillations and their stability are of special interest.